(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Bangka Island is the largest offshore tin mining in Indonesia conducted by companies and local communities, both legal and illegal. This could be alarming, for example Kelabat Bay which planned as a conservation area due to the impact of increase of suspended solid. This research aims to analyze the hydro-oceanographic conditions and Total Suspended Solid (TSS) distribution process due to tin mining in Bangka Waters, especially in Kelabat Bay. The method used was numerical modelling using MIKE 21 software to obtain hydro-dynamics data and TSS distribution due its sources from each mining spot with Flow Model Flexibel Mesh (FM) module and Mud Transport (MT) module. The model’s verification obtained 0.9435 correlation and 0.1611 Root Mean Squared Error (RMSE) for tidal data. The tailing will cause high TSS distribution in Bangka Waters especially for mining activities in shallow waters (<10 m) and nearby coast (<2 miles). The distribution of TSS in Bangka Waters will be dominantly carried towards the Bangka Strait. In Kelabat Bay itself, the TSS value is 0-25 mg/L and spread throughout the region with radius around 16 miles. The Bangka Waters, especially Kelabat Bay which planned as conservation area will be threatened by the increase of TSS due to offshore mining activities. It will become the recommendation for policy making in Bangka Belitung such as coastal and small islands zoning policy.